Thermal Behavior of Sr(II) and Ba(II)-Diclofenac Complexes in Solid State: Study of the Dehydration and Thermal Decomposition - Kobelnik, Marcelo; Cassimiro, Douglas Lopes [UNESP]; Santos, Diogenesdos Dos [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Wiley-Blackwell, 2011)
Solid state compounds of general formula Sr(Diclof)(2)center dot 5.7H2O and Ba(Diclof)(2)center dot 4.8H2O were obtained. Thermogravimetry (TG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and microscopy analysis were used to characterize these compounds. Details concerning the dehydration and thermal decomposition as well as data of kinetic parameters have been described here. The kinetic behaviors of these stages were evaluated from several heating rates with samples masses of 2 and 5 mg in open crucibles under a nitrogen atmosphere. The results of the present study improve the knowledge on these compounds including their dehydration and thermal stability. The obtained data depend on the mass of the sample which results in two kinetic behavior patterns.
Keywords: diclofenac; divalent metal ions; thermal behavior; kinetic parameters